Cardiovascular Disease-Related Serum Proteins in Workers Occupationally Exposed to Polycyclic Aromatic Hydrocarbons. (22nd June 2019) - Alhamdow, Ayman; Lindh, Christian; Albin, Maria; Gustavsson, Per; Tinnerberg, Håkan; Broberg, Karin
Abstract: Chimney sweeps have higher incidence and mortality of cardiovascular disease (CVD), likely related to their exposure to polycyclic aromatic hydrocarbons (PAH). In order to identify underlying mechanisms of PAH-related CVD, we here investigated whether PAH exposure was associated with levels of putative CVD-related proteins in serum among currently working chimney sweeps. We enrolled 116 chimney sweeps and 125 unexposed controls, all nonsmoking male workers from Sweden. We measured monohydroxylated PAH metabolites in urine by liquid chromatography coupled to tandem mass spectrometry and a panel of 85 proteins in serum using proximity extension assay. Linear regression analysis adjusted for age and body mass index showed that 25 proteins were differentially expressed between chimney sweeps and the controls ( p  <   .05, adjusted for false discovery rate). Of the 25 proteins, follistatin (FS), prointerleukin-16 (IL-16), and heat shock protein beta-1 (HSP 27) showed positive associations with the monohydroxylated metabolites of PAH in a dose-response manner ( p  <   .05). Pathway and gene ontology analyses demonstrated that the differentially expressed proteins were mainly involved in inflammatory response and immunological functions, such as leukocyte migration, cell movement of leukocytes, and adhesion of immune cells. In conclusion, we found a number of putative CVD-related proteins differentially expressed, between PAH-exposed and unexposed individuals, and mainly involved in inflammation and immune function. Our data warrant protective measures to reduce PAH exposure and longitudinal investigations of the protein profile in chimney sweeps and other occupational groups exposed to PAH.